Colony, Anderson County - Tinsley, Amber (Kansas State University, The Chapman Center for Rural Studies, 2012)
Originally called Divide, the town of Colony began as a tavern and later a depot on the Leavenworth, Lawrence, and Galveston railroad. In the early twentieth century, it was known as the "Hay Capital of the World."
Amber Tinsley, “Colony, Anderson County,” Chapman Center Research Collections, https://ccrsresearchcollections.omeka.net/items/show/136.
Keywords: Agriculture; Anderson County; Colony; Divide; Kansas; Railroad